2013
DOI: 10.1007/s11356-013-1505-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of treated wastewater irrigation on antibiotic resistance in the soil microbiome

Abstract: The reuse of treated wastewater (TWW) for irrigation is a practical solution for overcoming water scarcity, especially in arid and semiarid regions of the world. However, there are several potential environmental and health-related risks associated with this practice. One such risk stems from the fact that TWW irrigation may increase antibiotic resistance (AR) levels in soil bacteria, potentially contributing to the global propagation of clinical AR. Wastewater treatment plant (WWTP) effluents have been recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(64 citation statements)
references
References 111 publications
2
53
0
1
Order By: Relevance
“…The incidence of resistant microorganisms is monitored primarily in hospitals, but much higher risk is present in the soil and waters [3]. Resistance, generated in the external environment, is a natural development of every live system.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of resistant microorganisms is monitored primarily in hospitals, but much higher risk is present in the soil and waters [3]. Resistance, generated in the external environment, is a natural development of every live system.…”
Section: Introductionmentioning
confidence: 99%
“…The release of antibiotics together with the human-linked microbiota might be particularly important for the emergence of newly evolving antibiotic-resistant pathogens (1,14). Environmental reservoirs for antibiotic resistances, especially those affected by anthropogenic activities (e.g., application of manure), can serve as "hot spots" for the spread of antibiotic resistance genes and antibiotic-resistant bacteria through food and water, with unknown consequences for human health (14)(15)(16). D'Costa and colleagues indicated that soil could serve as an underestimated reservoir for antibiotic resistance that has already emerged or has the potential to emerge in clinically important bacteria (17).…”
mentioning
confidence: 99%
“…Similarly, the spread of antibiotic resistance in hospitals and in the environment has been extensively discussed and studied with over 850 publications. Many of the studies report an inventory of antibiotic resistance genes (Nesme et al 2014) and many address bacteria in aquatic environments (for review see Kümmerer 2009b) or soils (Gatica and Cytryn 2013). The resistance of bacterial species used as fecal indicators was also often investigated (Luczkiewicz et al 2013;Servais and Passerat 2009).…”
Section: Antibiotics In the Environmentmentioning
confidence: 99%